2001
DOI: 10.1165/ajrcmb.24.5.4320
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Asthma-like Responses in Different Mouse Strains by Oral Tolerance

Abstract: In this study we examined the effect of oral antigen (Ag) administration on the development of experimental asthma in different mouse strains. We selected BALB/c, BP2, CBA/Ca interleukin (IL)-5 transgenic, and BALB/c T-cell receptor-delta-deficient mouse strains because they exhibit different aspects of the asthma syndrome. Mice exposed to 1% ovalbumin (OVA), dissolved in the drinking water for 5 consecutive days, became unresponsive to subsequent immunogenic OVA challenges. This regimen of OVA administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
117
2
32

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(158 citation statements)
references
References 40 publications
6
117
2
32
Order By: Relevance
“…1). These results confirm that our protocol induces an intense eosinophilic inflammation (28). Intravenous LPS administration concomitantly with the second OVA challenge completely suppressed airway eosinophilia in the three mouse strains studied (Fig.…”
Section: Lps Administration Suppresses Allergic Airway Inflammation Tsupporting
confidence: 86%
See 3 more Smart Citations
“…1). These results confirm that our protocol induces an intense eosinophilic inflammation (28). Intravenous LPS administration concomitantly with the second OVA challenge completely suppressed airway eosinophilia in the three mouse strains studied (Fig.…”
Section: Lps Administration Suppresses Allergic Airway Inflammation Tsupporting
confidence: 86%
“…In our model, we found that immunized and OVA-challenged WT animals failed to develop a significant AHR to the spasmogen ␤-methacholine. Thus, to study AHR we used the BP2 mouse strain, which exhibits consistently larger AHR than most other mouse strains (28,34). As expected, immunized and OVA-challenged BP2 animals displayed an intense AHR response to ␤-methacholine (Fig.…”
Section: Systemic But Not Local Lps Administration Suppresses Ahrmentioning
confidence: 78%
See 2 more Smart Citations
“…In contrast, high-dose feeding of Ag induced clonal anergy and/or deletion that was not transferable (5)(6)(7)(8). Some studies have shown that high-or lowdose feeding of Ag prevents Th2-driven allergic inflammation such as bronchial eosinophilia (9 -11) and airway hyperresponsiveness (12,13). However, there have been few reports on whether feeding dose and regimen influence the effects of oral tolerance in Ag-induced lung inflammation in mice (14), which models certain aspects of human asthma.…”
mentioning
confidence: 99%